DANE STATYSTYCZNE JAKO ŚRODEK DOWODOWY W SPRAWACH NA TLE DYSKRYMINACJI POŚREDNIEJ W ZATRUDNIENIU - Czarnecki, Paweł (Zeszyty Prawnicze, 2017)
Statistical Data as a Means of Proving in Cases Based on Indirect Discrimination in Employment Summary The article concerns the issue of using statistical data to prove indirect discrimination in employment. The author analyzes admissibility of such proof and explains conditions that have to be meet to set up a case based on statistical data. Particularly, the statistics should cover enough individuals, should not illustrate purely fortuitous or short-term phenomena, and should appear to be significant. The article ends with a suggestion that employees should have better access to statistical data on the structure of the workforce at their workplace. It is because the mere availability of such data would have protective effect.